Hydrogeochemical characterization and quality assessment of groundwater resources in Amtali Upazila, Barguna: A study of coastal Bangladesh - Afroz Jahan; Sukhen Goswami; Md. Jakir Hossain; Sujan Mallik; Mehedi Hasan Ovi; Mahfuzur Rahman; Mahmud Al Noor Tushar; Sarmin Sultana; Dhiman Kumer Roy (Solid Earth Sciences, 2025)
The coastal regions of Bangladesh are highly vulnerable to saline water intrusion due to excessive groundwater abstraction, rising sea levels, and frequent tropical disasters. Among these, Amtali Upazila in Barguna District faces significant challenges in maintaining groundwater quality, necessitating a comprehensive assessment. This study evaluates the hydrogeochemical characteristics of groundwater and assesses its suitability for drinking and irrigation. To achieve this, groundwater samples collected from a deep aquifer (260–350 m) across 23 locations were analyzed using hydrogeochemical, geospatial, and statistical methods. The major ionic composition follows the order Na+ > Mg2+ > K+ > Ca2+ and HCO3– > Cl− > SO42− > NO3– for cations and anions, respectively. Piper and Gibbs diagrams classify the groundwater (GW) as Na–HCO3 type, with ion exchange and rock–water interactions being the dominant geochemical processes. Water quality indices, including the Water Quality Index (WQI) and Sodium adsorption ratio (SAR), Sodium Concentration (SC), and Kelly's Ratio (KR), indicate that 73.9 % of the samples are suitable for drinking, whereas most samples are unsuitable for irrigation. Multivariate statistical analysis (correlation matrix, cluster analysis, and principal component analysis) confirms that geogenic processes primarily influence groundwater quality. The findings provide critical insights for policymakers and local authorities in formulating sustainable groundwater management strategies, ensuring safe drinking water, and mitigating irrigation challenges in the region.